Kondisi Bakteriologis Air Sumur di Sekitar Tempat Pembuangan Akhir Air Dingin Kota Padang - Cici Wulandari; Nasril Nasir; Anthoni Agustien (Universitas Andalas, 2014)
A research on bacteriological condition of ground well water at Air Dingin, Padang was conducted from January to March 2013 at the Health Laboratory Agency (UPTD Balai Laboratorium Kesehatan) of West Sumatra. The water samples were collected by using purposive method at three sampling points in distances of 250 m, 350 m and 450 m from garbage disposal locations. Bacteriological test was done using Most Probable Number method (MPN) with combination of 3:3:3. Escherichia coli was described using indole, methyl red, voges proskauer, citrate (IMViC test). The result showed that MPN of Escherichia coli of ground well water for each distance of 250 m, 350 m and 450 m ranges from 0 cell/100 ml to 2400 cell/100 ml. Based on bacteriological parameter test, quality of the ground well water around the landfill area was not appropriate to be consumed by people, except for ground well water was located at 450 m from landfill.Key words: ground well water, Escherichia coli, landfill, qualilty.